A business case for scaling the production of tilapia in India: Synopsis of the Report and Major Recommendations - Panemangalore, Arun (WorldFish, 2022)
Brief on the scaling of production of tilapia in India. This document is prepared by WorldFish in collaboration with Confederation of Indian Industry.